2016
DOI: 10.1080/13102818.2016.1174078
|View full text |Cite|
|
Sign up to set email alerts
|

Preventive effect of doxycycline sponge against bisphosphonate-related osteonecrosis of the jaws: an animal study

Abstract: The aim of this study is to investigate the effect of doxycycline collagen sponge on bisphosphonate-related osteonecrosis of the jaw (BRONJ) and the level of serum biomarkers as an indicator of osteonecrosis. Twenty-four rats were divided into four groups. Animals in the control group were injected with saline and animals in Groups I, II and III were injected with zoledronate three times a week for eight weeks. After eight weeks, the following procedures were performed in each group. In Group I: extraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…Capar et al conducted a study aimed at determining the efficacy of collagen sponges with doxycycline for the purposes of ONJ prevention after extraction. This study proves that the preliminary application of such sponges for extraction, socket, and to cover the wound can be an effective method of preventing osteonecrosis [59].…”
Section: Antibioticsupporting
confidence: 58%
“…Capar et al conducted a study aimed at determining the efficacy of collagen sponges with doxycycline for the purposes of ONJ prevention after extraction. This study proves that the preliminary application of such sponges for extraction, socket, and to cover the wound can be an effective method of preventing osteonecrosis [59].…”
Section: Antibioticsupporting
confidence: 58%
“…In Çapar's study, MRONJ developed in rats clinically. Serum CTX, ALP (Alkaline phosphatase), and TRACP-5b biomarker levels were not statistically different between MRONJ and control groups (p>0.05) 24 . In our study, unlike this study, serum TRACP-5b value was found to be lower in the study group developing MRONJ than the control group.…”
Section: Discussionmentioning
confidence: 84%
“…The dose of Z.A. used in our study was determined to be 2.4 mg/ kg for each rat in accordance with similar studies [21][22][23][24] . In our study, zoledronic acid was given 0.2 mg/kg twice a week for 6 weeks to reach a total dose of 2.4 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lokal doksisiklin uygulaması ise periodontal patojenlere ve aktinomiçes türleri üzerine etkili olup; diş çekimi sonrası enflamasyonun azalmasını da sağlamaktadır. Çalışma sonuçlarına göre bu teknik, önleyici anlamda başarılı bulunmuştur 55 . Karasneh ve ark.…”
Section: Konservatif Tedavilerunclassified